UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN SISTEM REM KELAS XI SMK ISLAM SALAK BROJO PEKALONGAN TAHUN AJARAN 2014/2015 - Muh Fredy Hermawan; Tarto Sentono (Jurnal Taman Vokasi, 2016)
The purpose of this research to imporove the activity and student learning outcomes of class XI Islam Salak Brojo Pekalongan Vocational High School by audio-visual menthod on the brake system subjects.This education is clasroom action researsh that been conducted in Islam Salak Brojo Pekalongan.Vocational High School in the academic year of 2014/2015. The subject in this research is a class XI student of Light Vehicle Engineering Islam Salak Brojo Pekalongan Vocational High School that amounted to 26 student. The data collection techniques used observation and tests are divided into pre-test and post test. The data were anilyzed using descriptive statistics.The research result showed that the application of audio-visual method on the brake system subjects can improve activity and student learning outcomes class XI Islam Salak Brojo Pekalongan Vocational High Shool. The result can be seen in the successful development of the I cycle, the average value of learning activities amounted to 53,84 increased in the II cicle to 56,34 then on the III cycle increased to 59,42. On the learning outcomes of I cycle on average reached 5,11 increased in the II cycle to 6,51 then on the III cycle increased to 18,32. Therefore can be concluded that audio-visual method can increase the activity and student learning outcomes on theÂ  break system subjects of class XI student of Islam Salak Brojo Pekalongan Vocational High School.